An optimized three-laser 27-color spectral flow cytometry panel for multi-organ profiling in mice - Hyeonji Song; Yusik Lim; Jaechul Lim (PLoS ONE, 2026)
While high-dimensional flow cytometry plays critical roles in resolving complex cellular networks, there remains a scarcity of comprehensive panels for the simultaneous profiling of diverse mouse cell types, primarily due to the technical challenges of spectral overlap and the limited availability of mouse-validated reagents. To address this technical gap and resolve diverse cell populations in murine models, we designed a 27-color flow cytometry panel optimized for 3-laser spectral flow cytometers. This optimized panel enables broad and simultaneous detection of 16 distinct cell subsets from both lymphoid and myeloid lineages—including T cells, B cells, plasma cells, NK cells, innate lymphoid cells, dendritic cells, monocytes, macrophages, neutrophils, eosinophils, basophils, mast cells—along with non-immune cells, such as epithelial, endothelial, fibroblast, and neuronal-associated cells. The panel has been successfully applied to various tissues, including spleen, thymus, bone marrow, peripheral blood, mesenteric lymph nodes, peritoneal lavage fluid, gut epithelium, and lamina propria. Applying this panel to a poly(I:C) model, we successfully tracked systemic shifts in monocyte and neutrophil populations and identified a previously unrecognized, Cyp11b1 -expressing immune cell subset via reporter expression. This panel will facilitate high-dimensional immune profiling on standard 3-laser cytometers, providing a robust tool for dissecting cellular landscapes across diverse contexts.